Utilization mother and child health book on knowledge pregnant women - Retno Palupi Yonni Siwi; Erma Retnaningtyas; Anggrawati Wulandari; Nita Dwi Astikasari (Science Midwifery, 2023)
The low knowledge of pregnancy care is influenced by the lack of information so that it has an impact on the utilization of MCH book. The purpose of this study was to analyze the effectiveness of the use of the MCH book on knowledge about pregnancy care for pregnant women. This study used a correlational analytic with a cross sectional. The population in this study were 40 respondents with a total sample of 36 respondents using the simple random sampling technique. Data collection by using a questionnaire, statistical test Spearman Rank. The results showed that 36 respondents, almost half of the respondents used MCH book in the high category, namely 15 respondents (41.7%), most of the respondents had knowledge of good pregnancy care, as many as 26 respondents (81.2%) . The results of data analysis using the Spearman Rank obtained a P value of < 0.05 (0.000 < 0.05), which means that the use of MCH book is effective on knowledge about pregnancy care in pregnant women. The utilization of the MCH book as a source of information and medical records as well as an important communication tool and information medium for health workers, pregnant women and families.